Business cycle estimation with high-pass and band-pass local polynomial regression - Luis J. Álvarez (Econometrics, 2017)
Filters constructed on the basis of standard local polynomial regression (LPR) methods have been used in the literature to estimate the business cycle. We provide a frequency domain interpretation of the contrast filter obtained by the difference of a series and its long-run LPR component and show that it operates as a kind of high-pass filter, so that it provides a noisy estimate of the cycle. We alternatively propose band-pass local polynomial regression methods aimed at isolating the cyclical component. Results are compared to standard high-pass and band-pass filters. Procedures are illustrated using the US GDP series.
Keywords: C13; 330; business cycles; local polynomial regression; filtering; high-pass; band-pass; US cycles